Timing of food consumption in Hispanic adolescents with obesity. Issue 7 (28th December 2020) - Vidmar, Alaina P.; Jones, Roshonda B.; Wee, Choo Phei; Berger, Paige K.; Plows, Jasmine F.; Claudia Rios, R. D.; Raymond, Jennifer K.; Goran, Michael I.
Summary: Background: Little is known about the normal eating time periods in adolescents with obesity and how these patterns change throughout development. As the obesity epidemic continues to rise in adolescence, it becomes imperative to understand developmentally appropriate eating behaviours and to create weight management strategies that build on those innate patterns and preferences. The purpose of this study was to determine the most common habitual eating windows observed in adolescents with obesity. Methods: Participants were 101 Hispanic adolescents (mean age 14.8 ± 2.1 years; 48 male/53 female) with obesity (BMI ≥95th percentile) who were recruited as part of a larger clinical trial. Dietary intake and meal timing was determined using multiple pass 24‐hours recalls. Histograms were utilized to determine the natural distribution of percent consumption of total kilocalories, carbohydrates and added sugar per hour. Results: The majority of total kilocalories (65.4%), carbohydrates (65.3%) and added sugar (59.1%) occurred between 11:00 and 19:00. Adolescents were 2.5 to 2.9 times more likely to consume kilocalories, carbohydrates, and added sugar during the 8‐hour window between 11:00 am and 19:00 pm than other time windows examined (all P  < .001). The consumption of these calories did not differ between weekdays and weekend ( P  > .05) or by sex. Conclusions: In this cohort, more than 60% of calories, carbohydrates and added sugar were consumed between 11:00 am and 19:00 pm, which is concordant with an afternoon/evening chronotype that is common in adolescents. Our findings support this 8‐hour period as a practical window for weight loss interventions that target pre‐specified eating periods in this population.